PREPARATION AND ANALYTICAL STUDY OF RASKARPUR - Gayatri, Gaonkar S (International Journal of Ayurveda and Pharma Research, 2017)
Parad Murchana is the backbone of Rasashastra which is a branch of Ayurveda. Murchana signifies the formulations of mercury after Shodhan (purification). Parad can only be utilized therapeutically post Murchana. It is broadly classified into Sagandha (mercury with Gandhak) and Nirgandha (mercury without Gandhak) and each of it is further classified (for better learning) into Kharaliya, Parpati, Pottali and Kupupakva kalpanas, the later being better than the former with respect to its potency and action. This is due to the increased duration of Agni sanskara (heat given) as rightly quoted by Charaka in Charak Sanhita that Sanskar increases Guna (properties). Raskarpur is a Kupipakva-nirgandha kalpana. Nirgandha kalpana have always held a secondary status as compared to the Sagandha as the later are termed safer to use than the former. Mercury when combined with Gandhak (sulphur) becomes stable and less toxic. Nirgandha on the other hand needs to be administered in a proper dosage and for an appropriate duration only. This research is an attempt to study a Nirgandha kalpana and thus Raskarpur was taken . All the various versions of Raskarpur were studied and finally the Rastarangini version was selected. In order to bring uniformity in the drug prepared 2 batches of Raskarpur were prepared. This also helped to standardize the process. It was observed that the compound HgCl was formed at 100-1100. Raskarpur once prepared was tested for confirmation of the compound formed. During analysis 1 market sample was randomly taken and all 3 Raskarpur samples were analysed with their results compared with the standards. It was found that the percentage of Hg was very low as compared to the standards, that of the market sample being the lowest. The reason for the same needs to be evaluated. This study is a first attempt towards studying Raskarpur further research needs to be done using other versions.